The Use of a Rapid D-dimer Blood Test in the Diagnostic Workup for Pulmonary Embolism: A Management Study - de Groot, Marco R.; van Marwijk Kooy, Marinus; Pouwels, Jos G. J.; Engelage, Anneke H.; Kuipers, Bart F.; Büller, Harry R. (Thrombosis and Haemostasis, 1999)
Background. D-dimer assays have a potential to rule out pulmonary embolism in case of a normal test result. We studied the clinical utility of incorporating the SimpliRED D-dimer test result and clinical probability in the routine diagnostic work-up of patients with suspected acute pulmonary embolism. Methods. In a prospective management study 245 consecutive patients, hospitalised as well as outpatients, were included. A SimpliRED D-dimer test and perfusion/(ventilation) scintigraphy were obtained in all patients, whereas clinical probability was determined in the subgroup of patients with a non-diagnostic scan and normal D-dimer result. A diagnostic algorithm determined the necessity for further testing and decisions about treatment. All patients were followed up for 3 months. Results. In 54 patients (22%) with a normal lung scan and 50 patients (21%) with a high probability lung scan, antithrombotic therapy was withheld or started respectively, irrespective of the D-dimer result. A non-diagnostic lung scan was found in 137 (56%) patients, of whom 70 patients had an abnormal D-dimer test, in whom further testing was ordered. Of the remaining 67 patients with a non-diagnostic lung scan and normal D-dimer test 8 patients had a high clinical probability, and the subsequent ultrasonography and pulmonary angiography yielded pulmonary emboli in 1 patient. In the remaining 66 patients, pulmonary embolism was considered to be absent and antithrombotic treatment was stopped/withheld. During follow-up of these patients only one patient experienced a possible venous thromboembolic event (failure rate 1,5% ; 95% CI 0-8%). The SimpliRED D-dimer was normal in 6 of 61 patients with proven pulmonary embolism (sensitivity 90% ; 95% CI 80-96%). Conclusion. Our findings suggest that it is safe to withhold anticoagulant therapy in those patients with a non-diagnostic lung scan, a normal SimpliRED D-dimer test result, and without a high clinical probability. This results in a substantial decreased need for ultrasonography and pulmonary angiography. The SimpliRED should not be used in isolation to exclude pulmonary embolism.
Keywords: SimpliRED D-dimer; pulmonary embolism